1993
DOI: 10.1002/pca.2800040108
|View full text |Cite
|
Sign up to set email alerts
|

Annonaceous acetogenins: An updated review

Abstract: The Annonaceous acetogenins are an exciting new class of bioactive natural products whose antitumour, pesticidal and other bioactivities are due to inhibition of electron transport in mitochondria. This paper tabulates the 61 compounds in this class which have been published in the period of 1990-1992 and reviews recent progress with the chemistry and biology of these potent compounds. (Appendices will be published in the next issue.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
200
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 228 publications
(205 citation statements)
references
References 61 publications
4
200
0
1
Order By: Relevance
“…squamosa (96h LC 50 -36.19mg/l and 34.30mg/l) was more toxic than the other combination. It has been reported that the toxicity of anno-naceous acetogenins found cytotoxic and antitumor activity (Fang et al, 1993). It behaves as bioenhancer and enhances the antimicrobial effect of antibiotics many fold (Khanuja et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…squamosa (96h LC 50 -36.19mg/l and 34.30mg/l) was more toxic than the other combination. It has been reported that the toxicity of anno-naceous acetogenins found cytotoxic and antitumor activity (Fang et al, 1993). It behaves as bioenhancer and enhances the antimicrobial effect of antibiotics many fold (Khanuja et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Les acCtogCnines de sept espkces, A. bullata, A. cherimolia, A. densicoma, A. montana, A. muricata, A. reticulata et A. squamosa (2) ont fait pour le moment l'objet d7Ctudes approfondies. Annona senegalensis n'a jusqu'h prCsent fait l'objet d'aucune recherche dans ce domaine.…”
Section: Introductionunclassified
“…Annonaceous acetogenins, a relatively new [1][2][3][4][5] class of natural products isolated from the Annonaceae family, have attracted considerable attention in recent years. The unusually broad spectrum of bioactivity, especially the extraordinarily high cytotoxicity to a variety of tumor cell lines, shown by numerous members of this class of compounds have encouraged many synthetic endeavors.…”
mentioning
confidence: 99%